Alih Wahana Makna Puisi Chairil Anwar “Aku” ke dalam Skenario “Pahlawan Tanpa Nama” dengan Plot Linier - Felichyta Yuliarti Adenuswantantri (Saraswati)
Poem "Aku" is one of a collection of poems belonging Chairil Anwar. Each stanza in the poem "Aku" has the meaning of the spirit of the struggle for independence. The meaning can harks back to Indonesian freedom fighters of his time. Alih wahana to be one good means to channel the spirit of the meaning of the poem "Aku" into a scenario. Interested to alih wahana poem "Aku" into a scenario, will give birth to a new story that is tailored to the meaning of the poem "Aku". New stories are created can not be separated from the plot that determines the course of the story. Plots were used to determine the course of the story is a linear plot. Linear plot is a plot of all the conflicts that lead to the main character so that readers focused on the main issues. The use of these plots will create a new story with a hero character in accordance with the meaning of the poem "Aku". This scenario is expected to be the spirit of ancient warriors to the younger generations now in maintaining independence.Keywords: Poetry "Aku", Alih Wahana, scenario, linear plot